2000
DOI: 10.1590/s0100-83582000000300008
|View full text |Cite
|
Sign up to set email alerts
|

Capacidade de absorção de nutrientes do capim-mMarandu (Brachiaria brizantha) e da planta daninha malva (Urena lobata) em função do pH

Abstract: A capacidade competitiva entre plantas daninhas e cultivadas é influenciada por vários fatores, entre eles o pH do meio onde as plantas crescem. Dessa forma, analisaram-se os efeitos da variação do pH sobre o desenvolvimento e os teores dos nutrientes fósforo, potássio, cálcio e magnésio acumulado na parte aérea e nas raízes do capim-marandu (Brachiaria brizantha) e da planta daninha malva (Urena lobata). Para isso, foram preparadas soluções nutritivas com os seguintes valores de pH: 3,5; 4,5; 5,5; e 6,5. Os t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 11 publications
1
3
0
2
Order By: Relevance
“…In the present study, the calcium concentrations observed in shoots of Marandu and Xaraes were 5.88 and 7.40 g kg -1 , respectively, for both the second and third cuts. Thus, it is believed that fertilization with wood ash has increased the pH of the soil, providing nutrients and calcium assimilation for the plants, resulting in similar calcium concentrations as those found by Galo et al (1974) and Werner et al (1996) but returning higher concentrations than those reported by Costa et al (2006) and Souza Filho et al (2000).…”
Section: Resultssupporting
confidence: 61%
“…In the present study, the calcium concentrations observed in shoots of Marandu and Xaraes were 5.88 and 7.40 g kg -1 , respectively, for both the second and third cuts. Thus, it is believed that fertilization with wood ash has increased the pH of the soil, providing nutrients and calcium assimilation for the plants, resulting in similar calcium concentrations as those found by Galo et al (1974) and Werner et al (1996) but returning higher concentrations than those reported by Costa et al (2006) and Souza Filho et al (2000).…”
Section: Resultssupporting
confidence: 61%
“…Una de las características de las praderas degradadas es la presencia de altas poblaciones de malezas, que ocupan los espacios que van dejando los pastos, por lo que, eventualmente la competencia por agua, luz y nutrientes se vuelve crítica (38) . Las malezas pueden aprovechar estos recursos mejor que los pastos, ya que agrupan a diversas especies, con diferentes necesidades y habilidades y una distribución espacial y estado de desarrollo no uniformes (39) , por lo que tienen la capacidad de explorar más eficientemente el ambiente en busca de los factores esenciales para el crecimiento, reduciendo su disponibilidad para los pastos (40,41) .…”
Section: Rehabilitación De Potreros Mediante El Control Químico De Malezasunclassified
“…O desenvolvimento da atividade agrícola nos trópicos tem sido limitado pelo aparecimento de uma comunidade extremamente agressiva e diversificada de plantas colonizadoras de áreas secundárias. Na região amazônica, essa peculiaridade é especialmente marcante face à plasticidade adaptativa que essas espécies manifestam às condições ambientais predominantes na região (Souza Filho et al, 2000;Dutra et al, 2002).…”
Section: Introductionunclassified